ANALISA KEKUATAN STRUKTUR BAMBU PADA PEMBANGUNAN ENTRY BUILDING GREEN SCHOOL UBUD - I Nengah Sinarta; I Nengah Damara Putra; I Ketut Yasa Bagiarta (U Karst, 2020)
Bamboo has 1.000-4.000 kg/cm2 tensile strength, so it becomes a substitute for reinforced concrete steel reinforcement. Makes bamboo has the potential to continue to be developed as a construction material not only for simple buildings but for more complex buildings. The elastic nature of bamboo, the bamboo structure has a high resistance to both wind and earthquake, where the MOE (Modulus of Elasticity) of 178.758 kg/cm2, MOR (Modulus of Rupture) of 886 kg/cm2, and compressive strength of 347 kg of fiber parallel on cm2. Analysis using SNI 1727-2013 for loading, SNI 1726-2012 for earthquake loading. Modeling and analysis of internal forces on structures using the software Sap2000 ver.15. The results of the upper structure of the dimensions of the bamboo frame diameter  120 mm and bamboo rafts diameter  80 mm. The superstructure on the bamboo column diameter  150 mm and bamboo beam diameter 150 mm. Planning bamboo plates with diameter  80 mm. Substructure with concrete material the size of the footing 0.8 m x 0.8 m and 1.2 m x 1.2 m for anchor planning using bolt dimensions 12.7 mm with the number of bolts as many as two pieces.Bambu memiliki kekuatan Tarik sebesar 1.000-4.000 kg/cm2 atau setara dengan besi baja kualitas sedang sehingga dapat menjadi pengganti tulangan baja beton bertulang. Hal ini membuat bambu memiliki potensi untuk terus dikembangkan sebagai material konstruksi bukan hanya untuk bangunan yang sederhana namun untuk bangunan yang lebih kompleks. Sifat bambu yang elastis, struktur bambu mempunyai ketahanan yang tinggi baik terhadap angin maupun gempa, dimana MOE (Modulus of Elasticity) sebesar 178,758 kg/cm2, MOR (Modulus of Rupture) sebesar 886 kg/cm2, dan kuat  tekan sejajar serat sebesar 347 kg/cm2. Analisa dengan menggunakan SNI 1727-2013 untuk pembebanan, SNI 1726-2012  untuk  pembebanan  gempa.  Pemodelan   dan  analisa  gaya dalam pada struktur dengan bentuan software Sap2000 ver.15. Hasil upper struktur dimensi kuda–kuda bambu 120 mm diameter baut 15 mm sejumlah 1, usuk bambu diameter 80 mm, baut 8 mm berjumlah 1 buah. Super struktur pada kolom bambu berdiameter 150 mm dan balok bambu dengan  diameter  150 mm menggunakan  Perencanaan plat bambu dengan diameter 80 mm. Sub struktur dengan  bahan beton ukuran pondasi telapak 0,8 m x 0,8 m dan 1,2 m x 1,2 m untuk perencanaan angkur menggunakan diemensi baut 12,7 mm dengan jumlah baut yaitu sebanyak 2 buah.